Study of Helicobacter hepaticus in gallbladders with cholelithiasis and its sensitivity pattern - Pradhan, SB (Kathmandu University Medical Journal, 2010)
Background: Cholelithiasis is one of the most common digestive surgical disorders. The natural history of gallstone development is unknown. Bacteria are found in high concentration in bile and stone. It is difficult to ascertain whether bacterial infection of the bile arose before stone formation or vice versa. Materials & methods: Prospective study was carried out in 30 cholecystectomy specimens of patients with cholelithiasis collected from 15th January 2005 to 24th July 2005 in Department of Pathology, Kathmandu Medical College Teaching Hospital. The samples were collected in a sterile vial containing 0.5% saline. A small piece of gallbladder was taken in Blood agar and Chocolate agar media for micro anaerobic culture at 370C. The growth of the organism was observed after 48 hours of incubation. Gram stain and various biochemical tests were performed for the confirmation of Helicobacter hepaticus and its sensitivity pattern was studied. Histologically Helicobacter hepaticus was demonstrated in formalin fixed tissue sections using Warthin Starry Silver stain. Results: A total of 76.66% cases showed growth positivity. Nitrofurantoin was found to be the most sensitive drug (95.7%) for Helicobacter hepaticus followed by Ciprofloxacin (91.3%), Cephalaxin (91.3%), Certriaxone (91.3%), Ofloxacin (82.6%), Amikacin (65.2%) and Norfloxacin (60.9%). Helicobacter hepaticus was least sensitive to Amoxycillin (57%). Conclusion: From this study, it is quite apparent that Helicobacter hepaticus infection is commonly associated (76.66%) with cholelithiasis. If the patients are treated with the sensitive antibiotics regularly and the infection, that is the number one cause for the precipitation of bile leading to the formation of gallstones, can be controlled, the incidence of cholelithiasis can be reduced so that the health care expenditure related to gallbladder disease can be reduced markedly. Key words: Cholelithiasis Helicobacter hepaticus; WSS stain DOI: 10.3126/kumj.v7i2.2704 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 125-128